Toxoplasma gondii ADSL Knockout Provides Excellent Immune Protection against a Variety of Strains - Luyao Wang; Ding Tang; Chenghang Yang; Jing Yang; Rui Fang (Vaccines, 2020)
Toxoplasma gondii is a protozoan parasite, occurring worldwide, endangers human health and causes enormous economic losses to the Ministry of Agriculture. A safe and effective vaccination is needed to handle these problems. In addition, ideal vaccine production is a challenge in the future. In this study, we knocked out the adenylosuccinate lyase (ADSL) gene and found that the gene reduces the growth rate of T. gondii tachyzoites in vitro under standard growth conditions by plaque or replication experiments. Furthermore, mice that were immunized with tachyzoites of the ME49ΔADSL strain induced 100% protection efficacy against challenge with the type 1 strain RH, type 2 strain ME49 and type 3 strain VEG. All mice that were immunized with ME49ΔADSL had a survival rate of 100% when they were reinfected with wild-type strains, either 30 days or 70 days after immunization, and immunization was also protective against homologous infection with 50 T. gondii ME49 tissue cysts. In addition, the level of Toxoplasma-specific IgG was significantly elevated at 30 and 70 days after immunization. ME49ΔADSL induced high levels of Th1 cytokines (interferon gamma (IFN-γ), interleukin (IL)-12) at 4 weeks after immunization and spleen cell cultures from mice vaccinated for 150 days were able to produce robust INF-γ and IL-12 levels in the supernatant. The results of the present study showed that ΔADSL vaccination induced a T. gondii-specific cellular immune response against further infections. These results suggest that the ADSL-deficient vaccine can induce anti-Toxoplasma gondii humoral and cellular immune responses and has 100% immune protection against post-challenge by the type 1 strain RH, type 2 strain ME49 and type 3 strain VEG. It will be used as an excellent candidate for live vaccines and may contribute in a positive meaning to control human toxoplasmosis.